PENGARUH CERMIN REFLEKTOR TERHADAP DAYA DAN KENAIKKAN TEMPERATUR SEL SURYA - Heriyanto Rusmaryadi; Sukarmansyah .; Togar P.O Sianipar; Harry Setiadi (Jurnal Turbulen, 2018)
he purpose of this study is to determine the effect of the addition of reflectors to increase energy production and simultaneously to determine the change in temperature of solar cell as a result of the addition of the quantity of incoming sunlight. Capacity of the solar cell module is approximately 50 Wp, where the test is done from 9 am to 3pm for three days.The reflector's slope angle used is 1000, 1100, and 1200. The results of this study indicate an increase in output power of the solar cell module an average of 2.59% (with 4.42% at maximum).The side effect is the increase in maximum temperature of the solar cells by 0.60 C(or 1.59%).  Keywords: solar cell, reflector, slope angle, output power, temperature of solar cell